AB1148 Diagnosis of malignancies in children with musculoskeletal complaints. (23rd January 2014) - Russo, G.; Orlando, F.; Forni, C.; Battagliese, A.; Alessio, M.
Abstract : Background: Musculoskeletal pain is a frequent complaint in pediatrics in both tertiary and primary care. Although musculoskeletal symptoms are not usually related to severe disease, they can represent the first manifestation of an occult malignancy. When these complaints predominate in the clinical presentation, they lead the diagnosis towards nonmalignant conditions, that are most common cause of such symptoms in children, like injuries, nonspecific reactive arthritis or inflammatory connective tissue diseases. However, in acute lymphoblastic leukaemia, the most prevalent childhood malignancy, bone and joint pains are present early in 40-60% of cases and they frequently anticipate any abnormalities in complete blood counts. Objectives: To describe the clinical manifestations and complementary findings of the patients referred to a pediatric rheumatology unit with a final diagnosis of malignancy. Methods: Retrospective analysis of medical records from patients with final diagnosis of neoplasia attended at the Pediatric Rheumatology Unit of the Federico II University of Naples, Italy, between January 1990 and December 2010. Data on musculoskeletal complaints, clinical examination, laboratory tests, radiological studies and diagnostic procedures were obtained. Results: Of 2, 675 patients referred, 15 had a final diagnosis of neoplasia (0.56%) (8 M, 7 F, mean age 8 years, range: 4 - 15 years). Seven children were diagnosed with acute lymphoblastic leukemia, two with neuroblastoma, two with lymphoma, one with histiocytosis, one with Ewing's sarcoma, one with osteosarcoma and one with cerebral tumor. The most frequent symptoms were arthralgias (12/15, 80%), 4/15 children presented back pain, 2/15 patients presented polyarthritis, 1 child had myalgia. Nine children received a provisional diagnosis (60%): Juvenile idiopathic arthritis (JIA) was the most frequent (4/9), 3 children were diagnosed with rheumatic fever, 1 with Familial Mediterranean Fever, 1 with Systemic Lupus Erythematosus. The mean time between disease onset and final diagnosis was 3 months (range 1 – 12 months). Laboratory studies revealed anemia and a significant increase in sedimentation rate, lactate dehydrogenase and serum ferritin values; white blood cell and platelet changes were less frequent. Imaging studies contributed significantly to the diagnosis in 8 patients. The diagnosis was confirmed by bone marrow aspirate in 7 children with leukemia and by biopsies in those with bone tumor, lymphoma and histiocytosis. Conclusions: Malignancies should be considered in the differential diagnosis of children with musculoskeletal pain, because they are common at the onset of neoplasia, especially for acute lymphoid leukemia, and this possibility should be considered in the differential diagnosis of rheumatic diseases especially in the presence of abnormal laboratory (lactate dehydrogenase and serum ferritin) or imaging studies. The detection and resolution of mimicking symptoms require knowledge, skills, and a problem-solving attitude for musculoskeletal disorders. Before engaging in an extensive investigation, a careful history and full physical examination must be done. Disclosure of Interest: None Declared